CAPACITY BUILDING FOR STUDENTS AND ALUMNI AS CONTENT CREATORS BASED ON REPRODUCTIVE HEALTH ON SOCIAL MEDIA PLATFORMS AT THE MIDWIFERY DEPARTMENT OF POLTEKKES ACEH - Berkat, Satrinawati; Manaf, Salmiani Abdul; Sulastri, Sulastri (Department of Midwifery, Health Polytechnic of Aceh, 2025)
The Worldwide Digital Population estimates that by April 2023, there were 5.18 billion internet users worldwide, of whom approximately 4.8 billion, or 64.6%, used social media. Content creation has become a highly profitable profession. A content creator can earn a high income if they have a large following. By 2023, it is estimated that there will be 207 million content creators worldwide, with a total revenue of approximately USD 16.4 billion. Almost all midwifery students use social media. Some have thousands of followers. Generally, the content these students display is about daily life and remains simple. The purpose of this activity is to increase students' and alumni's knowledge of content creation and its benefits, improve students' and alumni's ability to create content on social media platforms, and create business opportunities for students and alumni by becoming content creators. Activity methods: Training, supervision, and monitoring. The training activity was held on August 24, 2024, and attended by 32 participants. Result of monitoring and evaluation: the end of 2024, 68% of training participants had created and uploaded reproductive health content on their social media accounts.